Company Valuation of PT Perusahaan Gas Negara TBK - Octaria Basri , Fira; Maya Damayanti, Sylviana (KnE Social Sciences, 2020)
More than decades, Indonesia’s economic growth depend on the oil and gas sector. In the past few years, oil and gas sector’s contribution to the state revenue decreased significantly along with the decline in reserves and production. The state revenue from the oil and gas industry decreased by almost 80 percent from Rp216 trillion in 2014 or 14 percent of state revenue to Rp44 trillion in 2016 or 2.8 percent of the state revenue. Perusahaan Gas Negara or also called as PGN is the largest national company in the natural gas transportation and distribution sector. In or der to make the business growing wider, PGN are going to acquiring Pertamina Gas or Pertagas. The acquisition is part of the establishment of the holding company in energy sector by the Ministry of State Own Enterprises, which was established on April 11, 2018. This research is made to know how the intrinsic value per share of Perusahaan Gas Negara (PGN) through calculating it with the discounted cash flow method using free cash flow to the firm. The data are obtained from PGN’s financial report from 2013 to 2018. The result is the intrinsic value per share of Perusahaan Gas Negara is IDR Rp6,757.72. Keywords: discounted cash flow, free cash flow to the firm, valuation.